Reflections on three years of teaching INTGLOS: Scaffolding as a strategy - Untalan, Al James C. (Animo Repository, 2014)
The paper is a reflection essay on the design and strategies the author have adopted in teaching Introduction to Global Society to freshman students for the past three years, 2011 to 2013. By analyzing the approaches used in the course (i.e., conducting class activities before the lectures, use of non-text-heavy slideshows, and giving out major exams with an objective and essay parts) and infusing the results of teaching evaluations conducted by the Institutional Testing and Evaluation Office, the author explored the underlying paradigm of his teaching method. Findings suggest that instructional scaffolding is evident because of a supportive learning environment and students are encouraged to have more active role in the learning process.